HUMAN AND CANID DIETARY RELATIONSHIPS: COMPARATIVE STABLE ISOTOPE ANALYSIS FROM THE KODIAK ARCHIPELAGO, ALASKA - West, Catherine F.; France, Christine A. (JOURNAL OF ETHNOBIOLOGY, 2015)
Stable carbon and nitrogen isotopes are used to address the dietary relationship between humans and two canid species at the Uyak site (KOD-145) on Kodiak Island, Alaska: dog (Canis familiaris) and red fox (Vulpes vulpes). We assess the relative contribution of marine and terrestrial protein to each species' diet as a measure of their dietary relationship to people, using zooarchaeological data, food web data, and ethnohistoric observations to interpret the results. The results suggest that dogs and foxes had different diets: the dogs are consistently enriched in both C-13 and N-15, which indicates a heavy dependence on marine protein, while the fox samples produced both marine and terrestrial isotope values. Data from this project have the potential to expand our understanding of human-canid relationships in this island environment and in the greater context of island ecology, and contribute some of the first isotopic data for small terrestrial mammals in the Gulf of Alaska.
Keywords: Canis familiaris; island ecology; Stable isotope analysis; Vulpes vulpes